Benign and malignant lesions of the breast: clinico-pathological perspective from a government teaching hospital in West Bengal, India - Sarkar, Saurav; Lahiri, Arista; Bandyopadhyay, Soumyajyoti; Das, Snehasish; Chakraborty, Tamal (International Surgery Journal, 2018)
Background: While breast cancer is one of the most commonly diagnosed cancer more than half of the women develop some benign disease of breast in their lifetime. The current study was conducted to describe the clinico-pathological findings associated with breast diseases and study their relationship. Methods: A record-based cross-sectional study was conducted on the samples of breast tissue obtained by fine needle aspiration cytology (FNAC) examination. The clinical variables like age, sex, presenting complaint, involved side (right/left/both) etc. were taken from the clinical notes sent, and nature of the aspirate, histopathological diagnosis, nature of the diagnosed disease (benign/malignant), and axillary metastasis were taken as variables from pathological examination. Results: The mean age of the patients was 33.49 years (±13.24 years) with majority belonging to 20-40 years. Among the 184 specimens examined, 94.57% belonged to female patients. The most frequent presentation was with lump (95.11%). Complaint arising out of right breast (47.83%) were higher compared to left breast (40.76%). Involvement of the supero-lateral quadrant was seen in 75.54%. In 30.44% of the cases the material was bloody or blood-mixed. Majority of the patients (86.41%) were diagnosed with benign disease commonest being fibroadenoma. Ductal carcinoma was the commonest malignant lesion. Younger age group, absence of bloody discharge and absence of peau d’orange were associated with benign lesion in a statistically significant way (p-value <0.001). Conclusions: In consonance with published literature the findings suggest association of older age group with malignant lesions. Blood-mixed aspirate, peau d’orange appear to be danger signs.